A systematic review of safety issues in tourism: Identifying emerging threats and proactive responses - Daeng Masiki, Andri; Suhardi, Bambang; Laksono, Pringgo Widyo (International Journal of Applied Sciences in Tourism and Events, 2025)
The study conducted a systematic review of seven scientific articles published between 2014 and 2024 to uncover emerging safety concerns in the tourism industry and suggest preventive measures. The identified safety threats in the sector include environmental risks, health issues, crime, terrorism, and digital dangers. Solutions like mobile safety apps and smart devices are being utilized to address these risks. The research aligns tourism safety strategies with Protection Motivation Theory (PMT) and proposes a multi-level intervention framework encompassing individual, organizational, and government actions. The study aims to contribute both theoretically by linking safety strategies with PMT and practically through the development of a comprehensive safety planning approach for sustainable tourism.